WOUND HEALING IN DIABETIC ULCER - Putra Pramana, Ida Bagus; Yasa, Ketut Putu (Medicina, 2012)
The mechanism of wound healing is a complex mechanism and involves a variety of cells. Injury is defined as a disruption of normal structure and function. Various types of growth factors and cytokines such as platelet derived growth factor and transforming growth factor beta involved in the mechanism of wound healing. There are four phases of wound healing mechanisms : hemostasis, inflammatory, proliferative, and remodeling. Diabetic ulcers is one major complication, occurring in 15% of patients with diabetes mellitus (DM) and as much as 84% of patients with diabetic ulcers require amputation action. In DM patients there is a failure in normal wound healing mechanisms. Various histopathological studies showed elongation phase of inflammation in patients with diabetes mellitus, thus inhibiting the formation of granulation tissue. Increased blood sugar levels will lower the expressin of perlecan, increased advanced glycation endproducts, decreased the formation of nitric oxide (by ± 67%), changes in the structure and function of fibroblasts and increased activity of matrix metalolproteinases, it will cause distruption of the normal wound healing mechanisms. (MEDICINA 2012;43:49-53).